Gender and HIV in Limpopo Province - Ali, Mohammed Abdosh (My University, 2009)
OBJECTIVE: To explore gender-related differentials of HIV prevalence in Limpopo Province, South Africa. METHODS: This is a cross-sectional study, data collected by the Rural AIDS and Development Action Research (RADAR) Program for the purpose of a controlled community trial in Limpopo Province. The study population consisted of 798 young men and 992 young women aged 14 to 25 years old. Subjects were tested for the presence of HIV antibodies and answered structured questionnaires. Logistic regression was used to examine risk factors related to gender differentials of HIV prevalence. RESULTS: The prevalence of HIV infection was 5.8% in men and 12.4% in women. Women often had older partners, while men had much younger partners or partners of a similar age. Men with primary education and reporting as students showed a reduced risk of HIV infection whereas unemployed women showed an increased risk of HIV infection. Sexual debut at the age of ≤ 16 was associated with increased risk of HIV infection among both sexes. A significantly higher HIV prevalence was found in women with more than four lifetime sexual partners, young women having an age difference of three to 9.9 years from their sexual partners, women having non-spousal sexual partners of 22 to 26 years of age, and women reporting no regular financial support. Frequency of sex of six to 20 times was a marker of increased risk of HIV among men. CONCLUSIONS: The risk of HIV infection was higher in young women than in men. The increased risk of HIV infection in women might be explained by social and behavioural factors that lead young women to select older partners, and is perhaps also a result of the biological susceptibility of women to HIV infection.
M.Sc. (Med.), Faculty of Health Sciences, University of the Witwatersrand, 2009
Keywords: gender; hiv